The World in Ruins: Heidegger, Poussin, Kiefer. Issue 2 (3rd July 2017) - Benjamin, Andrew
Abstract: The aim of this paper is to begin to respond to the question of how to engage the presence of catastrophic climate change as a locus of philosophical thought. What has to be thought is the end of the world. Central to that project is Heidegger's "The Origin of the Work of Art, " and in particular, Heidegger's thinking of the earth/world relation, both in itself and in terms of the limits it encounters. Heidegger's use of "examples" of artwork, as well as works by Nicolas Poussin and Anselm Kiefer, are deployed in order to begin to understand the role of art in thinking the end of the world.